Finding God in All the Black Places: Sacred Imaginings in Black Popular Culture - Smith-Shomade, Beretta E. (Rutgers University Press, 2024)
In Finding God in All the Black Places, Beretta E. Smith-Shomade contends that Black spirituality and Black church religiosity are the critical crux of Black popular culture. She argues that cultural, community, and social support live within the Black church and that spirit, art, and progress are deeply entwined and seal this connection. Including the work of artists such as Mary J. Blige, D’Angelo, Erykah Badu, Prince, Spike Lee, and Oprah Winfrey, the book examines contemporary Black television, film, music and digital culture to demonstrate the role, impact, and dominance of spirituality and religion in Black popular culture. Smith-Shomade believes that acknowledging and comprehending the foundations of Black spirituality and Black church religiosity within Black popular culture provide a way for viewers, listeners, and users not only to endure but also to revitalize.